Student participatory role profiles in collaborative science learning: Relation of within-group configurations of role profiles and achievement - Heinimäki Olli-Pekka; Volet Simone; Jones Cheryl; Laakkonen Eero; Vauras Marja (Elsevier, 2022)
During collaborative learning, students tend to spontaneously enact different participatory roles
that may significantly affect collaborative learning processes. Only few empirical studies to date
have investigated groups as systems based on emerging roles and role profiles of the participating
students, and how emerging role profile configurations affect achievement. This exploration of
students' self-adopted roles investigated the relationship between role profile configurations and
achievement. The statistically driven identification of role profiles was based on fine-grained
observations of student groups' interactions in two distinct collaborative science-learning settings.
While higher achieving groups typically exhibited versatile science-oriented role profile
configurations, opinion-based configurations prevailed in lower achieving groups. Although role
profiles with a social orientation were rare, a student with a distracting profile can have a significant
influence on group work. Consolidated by in-depth case examples, the findings highlight
the importance of understanding how collaborating groups' emergent role profiles dynamically
interact during collaborative learning and how different role profile configurations relate to
achievement.